PERAN AUDIT INTERNAL DALAM MENDUKUNG GOOD CORPORATE GOVERNANCE PADA PT. PELABUHAN INDONESIA IV (PERSERO) MAKASSAR - Andi Rustam; Faidul Adzim; Aulia Meilani (Jurnal Riset Perpajakan: Amnesty, 2018)
Research aims to determine if an adequate internal audt has a role in supporting good corporate governance effective at PT. Pelabuhan Indonesia IV (Persero) Makassar. This study was conducted using case study method with analytical descriptive method, while the population in this research is all employees who are in the Internal control unit and Corporate Secretary section. Research Data is obtained using questionnaires.  Based on the results of research conducted by the authors showed that adequate internal audit has a role in supporting good corporate governance effective at PT. Pelabuhan Indonesia IV (Persero) which means between internal audit in Implementation of GCG showing positive